2013
DOI: 10.1179/1362171813y.0000000134
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of friction-stir welding process using vibro-acoustic signal analysis

Abstract: This paper presents a mathematical model to predict the tensile strength (TS) of friction-stir welded (FSW) AA1050 aluminium alloy joint. This model has been obtained from the optimisation of the parameters of models developed from vibro-acoustic signals produced during the process. The multiple response method was used to obtain the optimisation model. During experimental development, the process parameters selected to be assessed were rotation speed (RS), travel speed, and tool profile (TP). The TS of the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…Therefore, apart from the expected disorder induced by the friction stir process, our Raman spectra reveal a successful GNS/AA1050 mixture. Similar Raman results were reported in References [17,30].…”
Section: Gns/aa1050 Composite Characterizationsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, apart from the expected disorder induced by the friction stir process, our Raman spectra reveal a successful GNS/AA1050 mixture. Similar Raman results were reported in References [17,30].…”
Section: Gns/aa1050 Composite Characterizationsupporting
confidence: 91%
“…disorder induced by the friction stir process, our Raman spectra reveal a successful GNS/AA1050 mixture. Similar Raman results were reported in References [17,30]. It was observed that the tool rotation speed was the most influential factor in the variation of the morphology and dispersion of the GNS within the metallic matrix.…”
Section: Gns/aa1050 Composite Characterizationsupporting
confidence: 88%
“…The evaluation of the ANN using the test data shows that a practically lineal relationship exists between the FSW parameters and the parameters calculated with the ANN by (1). Figure 8(c) shows the comparative analysis between the tensile strength obtained from the ANN-based model and the one determined using the mathematical model developed in previous works [23]. In this case, the value of the adjusted coefficient of determination 2 was 91.4% for mathematical model, indicating that less than 9% of the total variations are not explained by the model [22].…”
Section: Neural Network Evaluationmentioning
confidence: 83%